An innovative mode of whole-process non-contact single-person sample collection of nucleic acid testing (一种全程无接触式单人核酸检测样本采集创新模式) - ZHANG Lijun (张丽君); TANG Ling (唐玲) (中西医结合护理, 2022)
This paper introduced an innovative mode of whole-process non-contact single-person sample collection of nucleic acid testing. This aim of implementing this whole-process non-contact single-person sample collection mode is to reduce cross-infection, workload of sample collection and related health care costs. (本文介绍一种全程无接触式单人核酸检测样本采集创新模式, 旨在减轻减少交叉感染, 减轻医护人员核酸检测工作压力, 降低医疗成本。)